Some new and interesting desmids (Streptophyta, Desmidiales) from ephemeral puddles in the urban and industrial areas of Amsterdam (Netherlands) - van Geest, Alfred; Coesel, Peter (Phytotaxa, 2019)
From ephemeral puddles in the urban and industrial areas of Amsterdam (Netherlands) four new species are described: Cosmarium amstelodamense, C. galeatum, C. fruticosum and C. scutiforme. In addition, three previously described species causing much taxonomic confusion, viz. C. notabile, C. rostafinskii and C. benedictum, are reconsidered. Ephemeral puddles as potential habitat of rarely observed desmid taxa are briefly reviewed.